Absolute Eosinophil Counts and Colonic Mucosal Eosinophils Based on Inflammatory Bowel Disease Severity - Aulia, Nisma; Mulya, Deshinta Putri; Bayupurnama, Putut (Acta Interna The Journal of Internal Medicine, 2023)
Background. The inflammatory process in Inflammatory Bowel Disease (IBD) involves various types of inflammatory cells, including eosinophils. Eosinophils are not only associated with the severity of IBD but are also associated with clinical improvement. In contrast to the confirmed role of neutrophils, the role of eosinophils either in the blood or in the colonic mucosa of IBD patients have not been fully understood and confirmed.Objectives. To determine the difference in absolute eosinophil counts in the blood based on the severity of IBD and to determine the differences in the density of colonic mucosal eosinophil based on the severity of IBD.Methods. This is a cross-sectional study with consecutive sampling in the period August 2020 - July 2021. The research subjects were IBD inpatient or outpatient at Dr. Sardjito Hospital who met the inclusion and exclusion criteria. Researcher assessed data on absolute eosinophil counts in peripheral blood and eosinophil density in the colonic mucosa. The number of biopsies and the location of the biopsy were determined based on a colonoscopy performed by a Gastroentero-Hepatology Consultant. The calculation of eosinophils in the colonic mucosal tissue was carried out by an Anatomical Pathologist Specialist. IBD severity was assessed using the Truelove Witts score for Ulcerative Colitis (UC) and Crohn's Disease Activity Index (CDAI) for Crohn's Disease (CD) patients. Analysis using a computer program with a p value <0.05 was considered statistically significant.Results. There were 50 research subjects with a median age of 55 years (24-77 years). There was not a big difference between the number of male and female patients, namely 26 people (52%) vs 24 people (48%). The number of UC patients were dominant, namely 48 people (96%). The severity of IBD were divided into three groups with the number of patients with mild IBD were 22 (44%), moderate were 11 (20%), and severe IBD were 18 (36%). The number of patients with eosinophilia were 7 patients (14%) and colonic mucosal eosinophilia were 5 patients (10%). Kruskal Wallis test found that the mean absolute eosinophil blood in mild IBD was 21.45 cells/µL, moderate IBD was 25.50 cells/µL, and severe IBD was 30.44 cells/µL (p = 0.152). The mean of colonic mucosal eosinophils in mild IBD was 19.48 cells/hpf, in moderate IBD was 27.00 cells/hpf, in severe IBD was 32.03 cells/hpf (p = 0.023) and there was a statistically significant moderate correlation (r = 0.392; p = 0.005).Conclusion. There is no significant difference in absolute eosinophil counts in the blood based on the severity of IBD and there is a significant difference in the density of colonic mucosal eosinophil based on the severity of IBD.